Playthings of the Gods: On the “Magic Circle” Metaphor in Johan Huizinga’s Homo Ludens - De Kesel, Marc (Into the Magic Circle: Rethinking Homo Ludens, 2024)
In Johan Huizinga’s famous 1938 Homo Ludens: A Study of the Play-Element in Culture, “magic circle” is used a few times as a metaphor typifying the hallmark of “play”. This article focuses on the last pages of the volume, where the metaphor is mentioned twice for a reason that concerns Huizinga’s entire project. This close reading shows that the metaphor supports Huizinga’s attempt to save his play theory against the objection of relativism: his claim that “all is play” might be interpreted as discrediting all serious truth claims. The “magic circle of play” might call up the abysmal character of all theory, his own one included. The only remedy he apparently can come up with is to make an appeal to antique Platonism.